Scientometrics Today: Analysis of the Publication Activity of a Scientific Organization in the Russian Science Citation Index - Yu. D. Prokofieva; M. A. Peksheva (Библиосфера)
Due to the limited access to the Web of Science and Scopus, scientific libraries are forced to look for alternative sources of bibliometric information. There has appeared the need to revise the methods and tools for conducting scientometric research and assessing scientific activity in general. Specialists’ attention to the Russian Science Citation Index (RSCI) has especially increased, which now most fully reflects the Russian document flow on scientific publications and has the analytical capabilities necessary to work with bibliometric indicators. In the Central Scientific Library of the Ural Branch of the Russian Academy of Sciences (UB RAS), the methodology for scientometric analysis of the publication activity of scientific organizations of UB RAS has been reoriented to RSCI. The purpose of the study is to analyze the publication activity of a UB RAS scientific organization and test the RSCI tools for solving scientometric problems according to the developed methodology. The study revealed the need to revise the analysis criteria and methods of obtaining data according to the RSCI architecture. Conclusions are drawn on the effectiveness of RSCI tools for the purposes of the methodology, the correctness of the data obtained, and actions are proposed to improve the functionality of the system.